The Role of Legal Culture in Uzbekistan in Forming Youth Thinking and Worldview - Isayev Bekzod Bakhtiyarovich (Scientific Trends, 2025)
This article analyzes the current aspects of the process of improving legal culture in Uzbekistan, forming the legal thinking and worldview of young people. It also highlights the interrelationship of legal education, education and the social environment, and the role of legal consciousness in the development of the younger generation.
Keywords: Legal culture, legal consciousness, youth, legal education, worldview, legal thinking.